Clinical Methods in Medical Family Therapy - Mendenhall, Tai; Lamson, Angela; Hodgson, Jennifer; Baird, Macaran (Springer, 2018)
Medical family therapy (MedFT) represents a rapidly growing field in health care that purposefully interweaves patients and their families’ physical, psychological, social, and spiritual worlds. It does this with both scientific rigor and systemic training at its foundation. Originally coined in the 1990s, MedFT challenged outdated orthodoxies like mind-versus-body and nature-versus-nurture (McDaniel, Hepworth, & Doherty, 1992). The field has since served to bridge multiple facets of the healthcare system together, including collaborative and integrated behavioral healthcare (IBHC) research, training, policy, and practice (McDaniel, Doherty, & Hepworth, 2014; Hodgson, Lamson, Mendenhall, & Crane, 2014). Since these early beginnings, MedFT has grown in its visibility, scope, and influence across training programs, healthcare contexts, research, and policy discussions around the world. MedFTs are now serving as leaders in educational, research, policy, and clinical service settings wherever it is taught, studied, advocated, and provided. Its empirically rooted definition—aligning with efforts by Tyndall, Hodgson, Lamson, White, and Knight (2010)—is a field that is grounded in a BPSS [biopsychosocial-spiritual] perspective and marriage and family therapy, but also informed by systems theory. The practice of MedFT spans a variety of clinical settings with a strong focus on the relationships of the patient and the collaboration between and among the healthcare providers and the patient. MedFTs are endorsers of patient and family agency and facilitators of healthy workplace dynamics. (pp. 68–69) Guided by our passion to grow the field, we engaged the editor of Contemporary Family Therapy (Dr. Russell Crane) in 2010 to co-construct a special issue on MedFT. This then led to an exciting collaboration in 2014 to assemble an edited text through Springer called Medical Family Therapy: Advanced Applications. This landmark volume synthesized contemporary advancements in MedFT training, research, policy, and financial models (Hodgson, Lamson, Mendenhall, & Crane, 2014). It has been well-received by colleagues in practice, research, policy think tanks, and teaching/training sites—and serves as a go-to reference for practitioners, administrators, scholars, supervisors, and students/trainees alike. This new text, Clinical Methods in Medical Family Therapy, serves to highlight MedFTs in action across a variety of specialized healthcare settings. Alongside our own shared and respective areas of expertise, we have recruited and engaged skilled and innovative colleagues (including practitioners, theorists, supervisors, leaders, administrators, researchers, policy makers, and up-and-coming professionals)— most of whom identify as family therapists and/or medical family therapists—to describe the applications of MedFT within and across a myriad of care contexts and foci.